A discussion on "zhenren" in Chu bamboo and silk manuscripts. (March 2018) - Zhao, Ping'an
Abstract: Di Qi is called Di Zhen in " Tang zai Chimen " from the fifth volume of Tsinghua bamboo slip manuscripts. Di Zhen reminds us of Nü Tian in Chu silk manuscripts, which can be read as Nü Zhen, another name of Nü Wa . The world-creating god Nü Wa is called Nü Zhen because zhen ren seems to have enlarged its scope, from those who preserve their essence, or those who hold the Dao, to the Sage, the Perfect Man, and emperors. Di qi are also referred to as di zhen because they are the gods of earth. Moreover, Nü Zhen in the Chu Silk Manuscript also suggests its tendency to Daoism.